Profitability as a Review of Financial Performance (Case Study of PT. Gudang Garam Tbk) - Windi Atriani; Anwar Anwar; Nurman Nurman (Economos : Jurnal Ekonomi dan Bisnis, 2022)
This research is to determine the financial performance of PT. Gudang Garam Tbk is reviewed from the profitability ratio per quarter of the 2019-2021 period. The type of research used in this study is descriptive quantitative. The profitability ratios used in this study are Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Asset (ROA), Return on Equity (ROE), and Earning Per Share (EPS). The results of the analysis show that the gross profit margin (GPM) financial performance of the company's financial performance is categorized as poor because it is below the average standard of industry size and for NPM, ROA, ROE and EPS is included in the very good category because it is above the average standard size of the cigarette company industry listed on the Indonesia Stock Exchange.